Pengaruh Kombinasi Hypnobreastfeeding dan Aroma Terapi Rose terhadap Produksi ASI pada Ibu Menyusui di Wilayah Kerja Puskesmas Simpang Keramat Kabupaten Aceh Utara - Roza, Siska Desta; Novianti, Novianti; Sutrisna, Eka (Jurnal Sehat Mandiri, 2024)
This study focuses on the issue of breast milk production affecting the success of exclusive breastfeeding. It aims to analyze the effect of combining Hypnobreastfeeding with rose aromatherapy on breast milk production at Puskesmas Simpang Keramat. Using an experimental analytical design with a pretest-posttest one-group approach, the study involved 30 respondents divided into two groups: 15 in the intervention group receiving Hypnobreastfeeding and rose aromatherapy, and 15 in the control group with no intervention. The research was conducted from May to August 2024. Data were analyzed using the Shapiro-Wilk test for normality and independent t-tests for univariate and bivariate analysis. Results showed that the average breast milk production before the intervention was 370.6 ml in the intervention group and 366.0 ml in the control group. After the intervention, the average production increased to 442.0 ml in the intervention group and 382.3 ml in the control group. Statistical tests revealed a significant difference with a p-value < 0.05. The conclusion indicates a significant difference in breast milk production intensity before and after the intervention between the two groups. It is recommended that healthcare providers use the combination of Hypnobreastfeeding and rose aromatherapy to enhance breast milk production in breastfeeding mothers.